Feasibility of large language models for CEUS LI-RADS categorization of small liver nodules in patients at risk for hepatocellular carcinoma - Huang, Jiayan; Yang, Rui; Huang, Xiaotong; Zeng, Keyu; Liu, Yan; Luo, Jun; Lyshchik, Andrej; Lu, Qiang (Frontiers in Oncology, 2024)
BackgroundLarge language models (LLMs) offer opportunities to enhance radiological applications, but their performance in handling complex tasks remains insufficiently investigatedPurposeTo evaluate the performance of LLMs integrated with Contrast-enhanced Ultrasound Liver Imaging Reporting and Data System (CEUS LI-RADS) in diagnosing small (≤20mm) hepatocellular carcinoma (sHCC) in high-risk patients.Materials and MethodsFrom November 2014 to December 2023, high-risk HCC patients with untreated small (≤20mm) focal liver lesions (sFLLs), were included in this retrospective study. ChatGPT-4.0, ChatGPT-4o, ChatGPT-4o mini, and Google Gemini were integrated with imaging features from structured CEUS LI-RADS reports to assess their diagnostic performance for sHCC. The diagnostic efficacy of LLMs for small HCC were compared using McNemar test.ResultsThe final population consisted of 403 high-risk patients (52 years ± 11, 323 men). ChatGPT-4.0 and ChatGPT-4o demonstrated substantial to almost perfect intra-agreement for CEUS LI-RADS categorization (κ values: 0.76-1.0 and 0.7-0.94, respectively), outperforming ChatGPT-4o mini (κ values: 0.51-0.72) and Google Gemini (κ values: -0.04-0.47). ChatGPT-4.0 had higher sensitivity in detecting sHCC than ChatGPT-4o (83%-89% vs. 70%-78%, p < 0.02) with comparable specificity (76%-90% vs. 83%-86%, p > 0.05). Compared to human readers, ChatGPT-4.0 showed superior sensitivity (83%-89% vs. 63%-78%, p < 0.004) and comparable specificity (76%-90% vs. 90%-95%, p > 0.05) in diagnosing sHCC.ConclusionLLM integrated with CEUS LI-RADS offers potential tool in diagnosing sHCC for high-risk patients. ChatGPT-4.0 demonstrated satisfactory consistency in CEUS LI-RADS categorization, offering higher sensitivity in diagnosing sHCC while maintaining comparable specificity to that of human readers.